Super-resolution reconstruction for underwater imaging - Chen, Yuzhang; Li, Wei; Xia, Min; Li, Qing; Yang, Kecheng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In order to enhance the visual quality of images obtained by underwater imaging systems, super resolution (SR) reconstruction is introduced, including single-frame and multi-frame SR algorithms. Experimental images from a range-gated pulsed laser imaging system are processed by SR algorithms, results are evaluated and compared by blind, objective quality metrics. Results show that the image quality of underwater imaging can be effectively enhanced if the appropriate SR reconstruction algorithm is chosen.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 841-853
Keywords: optyka; super-resolution reconstruction; range-gated; quality metrics